2020
DOI: 10.1111/jgs.16657
|View full text |Cite
|
Sign up to set email alerts
|

Fatigability as a Predictor of Subclinical and Clinical Anemia in Well‐Functioning Older Adults

Abstract: BACKGROUND/OBJECTIVES: Anemia is a common condition in older adults for which fatigue, the primary symptom, often goes unrecognized as individuals typically equilibrate their activity to avoid fatigue. Whether assessing fatigability (i.e., susceptibility to fatigue) facilitates identification of anemia is unknown. This study examines the association between fatigability and prevalent, incident, and persistent subclinical and clinical anemia in well-functioning older adults. DESIGN, SETTING, PARTICIPANTS: Longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The differences in these ranges (0.9 g/dl in women vs 1.9 g/dl in men) result in different therapeutic guidelines, potentially leading to undertreatment of older women with anemia. Recently, Simonsick et al 55 examined fatigue and anemia in a cohort of older men and women from the Baltimore Longitudinal Study on Aging. They reported that even subclinical anemia, defined as Hb of 12–12.9 g/dl for women and 13–13.9 g/dl for men, was associated with fatigability.…”
Section: Defining Anemia Thresholds In Men and Womenmentioning
confidence: 99%
“…The differences in these ranges (0.9 g/dl in women vs 1.9 g/dl in men) result in different therapeutic guidelines, potentially leading to undertreatment of older women with anemia. Recently, Simonsick et al 55 examined fatigue and anemia in a cohort of older men and women from the Baltimore Longitudinal Study on Aging. They reported that even subclinical anemia, defined as Hb of 12–12.9 g/dl for women and 13–13.9 g/dl for men, was associated with fatigability.…”
Section: Defining Anemia Thresholds In Men and Womenmentioning
confidence: 99%